Opportunities and barriers of digitizing marketing strategies on the export of local export-potential products in Eastern Visayas the case of one town, one product next gen of the Department of Trade and Industry - Delos Santos, Angelica C.; Laurente, Jane Marie M.; Manota, Renelia B.
In conclusion, digital marketing plays a vital role in the growth and sustainability of local product exporters, particularly within the context of the OTOP Next Gen program in Eastern Visayas. By understanding and addressing the identified opportunities and barriers, policymakers, stakeholders, and businesses can collaboratively work towards fostering an environment conducive to digital marketing adoption, thereby unlocking the full potential of regional exports and driving economic advancement.